Why (agro)biodiversity is the lifeblood of the nexus approach - Estrada-Carmona, Natalia; Jones, Sarah (CGIAR, 2024)
A nexus approach shows that restoring wild and cultivated biodiversity (agro-biodiversity) is necessary for future food production.